2016
DOI: 10.1007/s10585-016-9822-x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between status of epidermal growth factor receptor mutation and distant metastases of lung adenocarcinoma upon initial diagnosis based on 1063 patients in China

Abstract: The study aimed to explore the correlations between status of epidermal growth factor receptor (EGFR) mutations and distant metastases. A total of 1063 patients with lung adenocarcinoma indentified with status of EGFR mutations from August 2010 to May 2015 at Shanxi Cancer Hospital were enrolled. 456 patients were confirmed with EGFR mutations. The associations among EGFR mutations, clinical factors, and distant metastases at initial diagnosis were evaluated. Patients harboring EGFR mutation were more likely t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…The possible reasons were as follows. Firstly, from the aspect of clinical characteristics between mutation subtypes, a retrospective study on 1,063 patients has demonstrated that exon 19 deletion rather than exon 21 mutation was associated with high incidence of developing BM during the course of therapy (38), which complied with the results founded in Li et al in 2015 (39). Another study further demonstrated that BM lesions with L858R mutation were located significantly closer to the brain surface (including preferential involvement of the caudate, cerebellum, and temporal lobe) than lesions with exon 19 deleted or wildtype EGFR (40).…”
Section: Discussionmentioning
confidence: 99%
“…The possible reasons were as follows. Firstly, from the aspect of clinical characteristics between mutation subtypes, a retrospective study on 1,063 patients has demonstrated that exon 19 deletion rather than exon 21 mutation was associated with high incidence of developing BM during the course of therapy (38), which complied with the results founded in Li et al in 2015 (39). Another study further demonstrated that BM lesions with L858R mutation were located significantly closer to the brain surface (including preferential involvement of the caudate, cerebellum, and temporal lobe) than lesions with exon 19 deleted or wildtype EGFR (40).…”
Section: Discussionmentioning
confidence: 99%
“…The NOS was used to perform quality assessment on all 22 studies and 14 (17,18,(25)(26)(27)(28)30,(32)(33)(34)(35)(36)38,42) high-quality and 8 (16,19,29,31,37,(39)(40)(41) as low-quality.…”
Section: Study Description and Quality Assessmentmentioning
confidence: 99%
“…Several studies have suggested that the cumulative incidence of brain as well as bone metastases may be higher in patients with EGFR+ NSCLC as compared to EGFR-wt [5][6][7]. Studies (N = 189-1063) evaluating bone and brain metastases at initial stage IV diagnosis have reported conflicting results [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%